Valoración del estado nutricional de los pacientes adultos en tratamiento de hemodiálisis y diálisis peritoneal del Centro de Cuidado Dialríos del Cantón Babahoyo-Los Ríos, en el periodo de mayo – septiembre 2019 - Ramos Mera, Meyling Yamile (2019)
The present work is oriented to carry out an evaluation on the nutritional status and lifestyle of the patients who are undergoing peritoneal dialysis and hemodialysis treatment, applied at the DialRíos Prevention Center of the City of Babahoyo. Chronic renal failure (CRF) is an asymptomatic pathology, of which symptoms only occur when the disease has progressed to the terminal phase, for this reason it is important to prevent and detect renal failure early, defining the CRI as the loss of the basic functions of the kidney, being diabetic nephropathy and arterial hypertension one of the first causes of the appearance of this disease worldwide. The objective of the study is to determine the influence of nutritional status in adult patients with end-stage chronic renal failure undergoing hemodialysis and dialysis attending the DialRios dialysis center. The methodology is quantitative, it will have a descriptive cross-sectional design. As a result, according to the age corresponding to adults aged 30-59, they have a simple relative frequency of 25%, while adults over 60 years of age have a simple relative frequency of 55% of the total population. Concluding these results, it is possible to identify patients at risk early, which allowed the development of a Healthy Eating plan.